Analisis Kinerja Keuangan Bank Syariah Indonesia dengan Menggunakan Metode Eagels Periode 2018-2020 - Maghfirah, Nur; Anggraini, Tuti (Jurnal Ilmiah Ekonomi Islam, 2022)
Bank Syariah Indonesia is one of the banks that offers various types of products and services. In 2018, Bank Syariah Indonesia faced high challenges. Indonesia's unfavorable economic conditions have an impact on the customer's financing business so that their finances decline. The decline in the quality of productive assets in 2018 prompted the company to increase reserves for asset losses, so that profits in 2018 were under pressure. This study aims to analyze the financial performance of Indonesian Islamic Banks using the EAGLES assessment aspect.This type of research is quantitative descriptive. This research describes systematically, factually, and accurately about the facts and characteristics of a particular population, or tries to describe the phenomenon in detail. In this study the data source used is secondary data. Aspects used to measure the financial performance of Bank Syariah Indonesia, namely, the ability to generate, asset quality, growth rate, liquidity, equity and strategic management.The results showed that the financial performance of the Indonesian Islamic Bank in terms of earning ability with ROA and ROE ratios obtained an average ratio of 0.25% and 3.11%, respectively. Judging from the aspect of asset quality, the NPF ratio obtained an average of 5.94%. The growth rate aspect which consists of the DGR and LGR ratios has an average ratio of 8.63% and 15.59%, respectively. Judging from the liquidity aspect with the FDR ratio, the average ratio is 23.33%. The equity aspect using the CAR ratio obtained an average of 12.55%. Judging from the strategic management aspect, the SRQ By Personnel ratio shows an average of 46.80%. Based on the results of the study, it can be found that the financial performance of Indonesian Islamic Banks in terms of the ROA and ROE ratios shows poor financial performance. The NPF and DGR ratios show a fairly good financial performance. Judging from the SRQ by Personnel ratio, it shows poor financial performance. Meanwhile, from the ratio of CAR, LGR and FDR, the financial performance of Bank Syariah Indonesia shows a very good performance.